Pelatihan E-commerce untuk Pemberdayaan Ekonomi Santri: Studi Kasus Pondok Pesantren Al Jauharen - Habibi, Akhmad; Sofwan, Muhammad; Mukminin, Amirul; Sofyan, Sofyan (Laboratorium Pembelajaran FKIP Universitas Jambi, 2025)
The digital era presents challenges and opportunities for Islamic boarding schools to empower students in the field of entrepreneurship. Training on the use of digital e-commerce platforms at the Al Jauharen Islamic Boarding School in Jambi aims to improve students' entrepreneurial skills and interests. This activity uses a participatory approach through theory, practice, and mentoring sessions. A total of 30 students took part in the training, with pre-tests and post-tests used to measure understanding. The results showed that 85% of participants experienced an increase in understanding, and 78% were interested in starting an independent business. Several students have succeeded in marketing products through platforms such as Shopee and Instagram. The obstacles faced include time management and limited access to technology. This training is effective in improving digital skills and entrepreneurial motivation, but requires further mentoring and technological support so that students' businesses are sustainable. With these positive results, it is hoped that similar training can be implemented in other Islamic boarding schools as an effort to empower the economy and develop students' competencies in the digital era. Keywords: e-commerce, digital literacy, entrepreneurship, Islamic boarding schools, economic empowerment